How many AIDS epidemics can occur in São Paulo city? - Breno Souza de Aguiar; Cassia Maria Buchalla; Francisco Chiaravalloti Neto (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE An ecological study describring the spatial characteristics of AIDS in São Paulo city between 2001 and 2010 according to the place of residence of reported cases in adults. METHODS The AIDS reported cases (28,146), grouped by sex, were geocodified (25,969) and linked with a census tract database (18,953). Case and population at risk data supplied spatial cluster identification and relative risk estimate by the scan method, using the discrete Poisson model. Incidence rate and proportional distribution allowed comparing people living in the high-risk clusters areas to other locations by age, race/ethnicity, schooling and transmission category. RESULTS The AIDS incidence rate decreased in both sexes except among young men and older people. The identification of spatial high-risk clusters showed that the decrease of AIDS did not occur in the same way in the city. Clusters located in the central area presented the highest AIDS incidence rates (245.7/100,000 men), especially among black women (RR = 7.9), men who have sex with men (66.2%) and injection drug users (10.7%) participation. In peripheral clusters, identified only in the female population, the epidemic can be related to the poverty of these women (22.5% low education level). Residents in the north and central-south areas of the city are generally black, with little schooling, and predominantly heterosexually infected. CONCLUSIONS The study of spatial clusters using a census tract helps to determine epidemiological patterns inside the city and in specific populations. Spatial stratification and key population epidemiological patterns were identified in four regions in São Paulo city.